Desmoplakin and clinical manifestations of desmoplakin cardiomyopathy. Issue 15 (5th August 2021) - Yuan, Zhong-Yu; Cheng, Li-Ting; Wang, Ze-Feng; Wu, Yong-Quan
Abstract : Abstract: Desmoplakin (DSP), encoded by the DSP gene, is the main desmosome component and is abundant in the myocardial tissue. There are three DSP isoforms that assume the role of supporting structural stability through intercellular adhesion. It has been found that DSP regulates the transcription of adipogenic and fibrogenic genes, and maintains appropriate electrical conductivity by regulating gap junctions and ion channels. DSP is essential for normal myocardial development and the maintenance of its structural functions. Studies have suggested that DSP gene mutations are associated with a variety of hereditary cardiomyopathy, such as arrhythmia cardiomyopathy, dilated cardiomyopathy (DCM), left ventricular noncompaction, and is also closely associated with the Carvajal syndrome, Naxos disease, and erythro-keratodermia-cardiomyopathy syndrome with skin and heart damage. The structure and function of DSP, as well as the clinical manifestations of DSP-related cardiomyopathy were reviewed in this article.